Gastric ulcer protective property of calcium channel blockers in male albino rats - B. KADALMANI; M. SARAVANA KUMAR; P. REVATHI; K. PRAKASH SHYAM (International Journal of Pharma and Bio Sciences, 2011)
Calcium ions have been considered as a serious contender for the development of various types of ulcers. Calcium ion influx seems to play an essential role in the stimulation- secretion coupling in mammalian oxyntic cells, an effect that can be inhibited by the calcium channel blockers. Calcium channel blockers (CCBs) are a class of drugs and natural substances that disrupt the calcium (Ca2+) conduction of calcium channels, the present study aims to evaluate comparative effect of Verapamil, Nifedipine, Diltiazem and Ranitidine against gastric ulcers induced in rats. The study was carried out in Sixty Wistar male albino rats (180–220 g) as two phase simultaneous study, one as acute and the other evaluated chronic effect. Gastric Ulcer was induced using aspirin (200 mg/kg) body weight (b.w) and treated orally using Verapamil (40mg/kg b.w) Nifedipine (40mg/kg b.w), Diltiazem (60mg/kg b.w) and Inj. Ranitidine 50mg/kg b.w intraperitoneally. The rats were anaesthetised under ether; Ulcer Pulse and Index were calculated.The results of comparison indicate that Nifedipine had shown but highly significant ulcer protective effect in both acute and chronic studies, than Verapamil, Diltiazem and Ranitidine.